Enhancement of Naphthalene Biodegradation by Sulfate Application in Brackish Subsurface Systems - Shafieiyoun, Saeid; Ismail, Reem; Al-Rauosh, Riyadh I. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Anaerobic biodegradation is the most dominant mechanism in the petroleum hydrocarbon contaminated subsurface systems. Due to depletion of terminal electron acceptors such as sulfate, anaerobic degradation of organic contaminants can be restricted. Hence, engineered sulfate application has been proposed as an effective remediation strategy to enhance the activities of sulfate reducer bacteria (SRB) in the contaminated subsurface systems. However, biodegradation process is significantly affected by environmental conditions and sulfate application in the contaminated saline and brackish coastal regions is unknown. A series of flow-through reactors (FTRs) representative of dynamic anaerobic subsurface conditions were conducted using undisturbed soil samples collected from brackish (semi)-arid coastal environments in Qatar. Dissolved naphthalene as one of the most dominant petroleum hydrocarbons that can be found in most of the contaminated sites was injected into FTRs under different salinity conditions. The relevant geochemical indicators as well as soil adsorption and dissolved phase concentrations were measured. The results confirmed development of reducing conditions as well as SRB activity under experimental conditions. Salinity did not restrict bioremediation and dissolved naphthalene degradation was more stable and enhanced under brackish water conditions because microbial cultures within the undisturbed soil were adapted to the brackish water conditions at the field sampling environment. This paper will provide an overview of the flow-through experiments and key findings.